Big data, Bigger privacy concern? - Dreyer, Nicolaus (2017)
In light of the rapid growth of big data applications in times where the internet of things is taking over personal privacy, this paper studies the area where data analytics and privacy concerns overlap. Identifying that anonymization and consent frequently do not suffice for user data, this paper also points out the weaknesses of regulations. A survey with 200 respondents showed that the awareness of big data capabilities caused significant privacy concern and willingness for (counter-) action, thus emphasizing that big data-driven firms should take a possible shift in user perception and behavior into account when formulating their strategy.